(untitled) (Plant Tissue Culture and Biotechnology, 2022)
An efficient in-vitro micropropagation protocol has been developed for Berberis chitria (Lindl.) - a rare medicinal plant from Himachal Pradesh, India using seeds and in-vitro nodal explants. The effects of different concentrations of BAP and GA3 for in-vitro seed germination was investigated and consequently 6.0 mg/l BAP + 0.0 mg/l GA3 was reported to be excellent for seed germination. Callus induction from leaf explants from aseptically grown seedling were also studied by using various concentrations of BAP and 2, 4-D and showing 94.26 ± 0.12% response at the concentration of 2.0 mg/l BAP + 0.4 mg/l 2, 4-D. The highest percentage of multiple shoot induction was obtained (100.00 ± 0.01% with an average of 4.50 ± 0.3 shoots) on MS medium augmented with 6.0 mg/l BAP + 1.0 mg/l Kn + 1.0 mg/l IAA. Whereas, the combined concentration of 1.0 mg/l NAA + 1.0 mg/l IBA + 0.5 mg/l IAA showed highest (76.05 ± 0.09%) root induction with an average of 3.84 ± 0.27 roots per shoot. The survival rate of these plantlets under greenhouse condition was 85%. This research communication provides first record about the in-vitro multiplication of B. chitria, collected from Himachal Pradesh Himalayas of India. Plant Tissue Cult. & Biotech. 32(2): 227-236, 2022 (December)